Pengaruh Pembelajaran Kooperatif Tipe Student Facilitator And Explaining Terhadap Kemampuan Komunikasi Matematis Siswa SMP Negeri 2 Somagede - Febri Intan Ratmadani; Ahmad Ahmad (AlphaMath : Journal of Mathematics Education, 2019)
This study aimed to detemine whether Student Facilitator And Explaining cooperative learning model affected students mathematical communication skills. The research design used was Posttest Only Control Design. The population in this study was entire seventh grade students in SMP Negeri 2 Somagede. Sampling was determined using Cluster Random Sampling technique. Two classes of sample were obtained. Class VII B, consistend of 23 students, selected as the experimental class which employed cooperative tipe Student Facilitator And Explaining learning model and class VII D, consisted of 23 students, was as the control class which used direct learning. Research results indicated that mathematical communication skills of students who attended Student Facilitator And Explaining learning was better than that of students who attended direct learning. So it can be interpreted that Student Facilitator And Explaining learning cooperative model affected students mathematical communication skills